Relationship between happiness, personal factors, self-esteem and lifestyles in the retired elderly. - Karuhadej, P.; Vorasiha, P.; Dangthongdee, S.; Cherwanitchakorn, S.; Shuaytong, P. (Chulalongkorn Medical Journal, 2023)
Background : Retired elderly should perceive and be ready to face physical, mental and social changes. They could appropriately adapt to live happily for the latter part of life. The researchers were interested in this topic and could modify the result to promote happiness for the retired elderly. Objectives : To study the levels of happiness in the retired elderly and their association with personal factors, self-esteem and life styles. Methods : Ninety-three samples were selected by simple random sampling from the retiree of Suan Sunandha Rajabhat University. Data were collected by mailed questionnaire which consisted of the questions constructed by the researchers, Oxford Happiness Questionnaire and Self Assessment of Coopersmith (1981). Cronbach coefficient of reliability for happiness, self-esteem and life styles were 0.74, 0.74, and 0.60 respectively. Data were analyzed in terms of percentage, mean, standard deviation, Chi-square test and Pearson’s Product Moment Correlation Coefficient. Results : The study found that the happiness is the most not specify happy or unhappy 63.4 % , followed by nearly unhappy and nearly happy 35.5% and 1.1 % respectively. The statistically significant factors (P < 0.05) associated with happiness were positive association in self-esteem (r = 0.581), occupation life styles (r = 0.291), exercise life styles (r = 0.277), and negative association in elderly age (r = - 0.218). The non-significant factors (P > 0.05) associated with happiness were general life styles, eating life styles, physical and mental health care, social assistance in everyday life,sex ,marital status, education, classify of work, monthly income, sufficiency income and healthy welfare. Conclusion : Government agencies should promote happiness in the retired elderly by promoting self-esteem, exercise, and occupation.